Legal Compliance Costs and Regulatory Quality in Vietnam’s Business Environment: A Case Study of Decree No. 46/2026/ND-CP - Thuy, Phan Thi Thanh (VNU Journal of Science: Legal Studies; Article in press, 2026)
In Vietnam, the term "legal compliance costs" is often simplistically understood as the expenses businesses must pay to complete administrative procedures. In reality, costs of legal compliance also arise from the design, enactment, and enforcement of laws. Furthermore, it serves as the most critical indicator for evaluating regulatory quality in business. This article explores the core components costs of legal compliance and clarifies the relationship between these costs and regulatory quality. By examining the case study of Decree No. 46/2026/ND-CP, which guides the implementation of the Law on Food Safety and was enacted and took effect on the exact same day, January 26, 2026, this paper highlights the unreasonable compliance costs businesses endure due to unstable regulatory quality. Consequently, the article proposes solutions to optimize costs of legal compliance and improve regulatory quality during the law-making process in Vietnam..